Fire-Resistant Rigid Urethane Foam Composition and Manufacturing Method
Patent Information
- Application Number
- KR1020250199107
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2045-12-15
Smart Images

Figure 112025141507289-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a flame-retardant rigid urethane foam applicable to fields requiring high flame resistance and structural stability, such as building interior materials, insulation materials, and industrial cooling or thermal insulation panels, and a method for manufacturing the same.
[0002] In particular, the technology relates to a flame-retardant rigid urethane foam that suppresses flame spread and smoke generation by forming a dense and strong carbonized protective layer upon combustion by including a phosphor-based flame retardant (a mixture of APP and DOPO), silica aerogel, aluminum hydroxide, carbon black, and surface-treated coffee grounds in the polyol composition. Background Technology
[0003] Rigid polyurethane foam has been essential in various fields, such as building insulation, panels for refrigeration or cold storage facilities, and industrial protective materials, due to its excellent thermal insulation, lightweight, and strength characteristics based on its closed-cell structure.
[0004] In particular, due to the tightening of building energy efficiency standards, the expansion of refrigeration and cold chain logistics facilities, and the increasing demand for high-performance panel systems, the market application of rigid polyurethane foam is expanding further because of its superior performance. However, due to the structural characteristics of organic polymers, problems such as surface melting and carbonization, rapid internal collapse, high heat release rates, and smoke generation exist when exposed to flames; this makes it difficult to meet fire safety standards required by ASTM E84, KS F ISO 5660, and FM 4880. Conventional methods of simply incorporating flame retardants involve a trade-off where improved flame retardancy is accompanied by a decrease in thermal insulation and mechanical strength. Furthermore, problems such as cell failure, non-uniform foaming, and increased brittleness have recurred due to poor dispersion of the flame retardants. General polyurethane foams are composed of organic polymer chains and a large amount of flammable foaming gases; consequently, when exposed to flames, the surface melts or carbonizes within a short period, and the internal cell structure collapses, leading to a tendency for the fire to spread rapidly. As a result, urethane panels installed in buildings can contribute to the initial spread of fire, so international and domestic standards such as ASTM E84 Class A, KS F ISO 5660, and FM Approvals 4880 require high flame retardancy, low smoke generation, and the maintenance of structural stability as essential conditions. However, the simple addition of flame retardants applied in conventional technology has a fundamental limitation in that it causes a trade-off between flame retardant performance and mechanical properties, and side effects such as increased thermal conductivity, cell breakdown, and increased brittleness of the foam have been frequently reported depending on the type of flame retardant, particle size, or dispersibility.
[0005] In particular, phosphate- or chlorine-based flame retardants such as APP (ammonium polyphosphate), TCPP (tris(1-chloro-2-propyl) phosphate), and TDCP can impart a certain level of flame retardancy, but they lack sufficient thermal stability at high temperatures, leading to problems where decomposition byproducts generate additional smoke or harmful substances during combustion. Furthermore, if the flame retardant is not uniformly dispersed within the foam, localized cell weakening, foam non-uniformity, and reduced hardness occur, causing a decrease in thermal insulation performance and structural reliability. For this reason, the structural contradiction in which increasing flame retardancy leads to a decrease in thermal insulation and compressive strength has been recognized in the field as a major constraint on technological development.
[0006] Meanwhile, there has been a continuous demand in industrial settings for the development of composite-based urethane foams capable of achieving high flame resistance while maintaining high mechanical performance, and various flame-retardant technologies have been proposed as prior art to address this. For example, Korean registered patent No. 10-2687005 presents a flame-retardant rigid polyurethane foam with a peak strength retention rate (P1 / P2 × 100) of 85% or higher in high temperature* and high humidity environments, and a composition controlling the thermal oxidation characteristics of the foam has been introduced to improve moisture resistance and heat stability. However, this technology has limitations in that it focuses on improving the strength retention rate, thereby limiting improvements in performance elements directly related to fire safety, such as ignition delay, suppression of combustion spread, and reduction of smoke generation.
[0007] Furthermore, Korean registered patent No. 10-1970842 discloses a general technology for manufacturing a rigid urethane foam by reacting a polyisocyanate, a polyol, a blowing agent, and one or more flame retardants; this follows a typical structure in which basic flame retardancy is secured by adding the flame retardant into the foam. However, the method of simply incorporating the flame retardant still contains structural limitations that make it difficult to achieve a balance between flame retardancy and mechanical performance due to issues with the flame retardant's dispersibility and compatibility with the polymer matrix.
[0008] In addition, Korean registered patent No. 10-2058227 discloses a technology regarding a method for manufacturing a rigid polyurethane foam or a rigid polyisocyanurate foam using an aromatic dicarboxylic acid-based polyetherester polyol. Prior art literature
[0009] Korean Patent Registration No. 10-2687005 Korean Patent Registration No. 10-2687005 Korean Patent Registration No. 10-1970842 The problem to be solved
[0010] The objective of the present invention is to provide a flame-retardant rigid urethane foam capable of effectively blocking oxygen access during combustion and suppressing flame spread and reducing the generation of smoke and toxic gases by forming a high-strength carbonized protective layer. Furthermore, the invention aims to ensure not only simple flame-retardant performance but also the stability of the foam structure, mechanical strength, and uniformity of the manufacturing process while maintaining or enhancing the thermal insulation function, which is an advantage of existing urethane foams. Moreover, the invention seeks to solve the technical problem of satisfying low smoke generation indicators while achieving ASTM E84 Class A level flame-retardant performance by uniformly dispersing a phospho-based flame retardant, silica aerogel, and aluminum hydroxide throughout the foam to exhibit a composite flame-retardant synergy. means of solving the problem
[0011] The present invention solves the above technical problem by using a composition based on a polyol that includes a phosphor-based flame retardant (a mixture of ammonium polyphosphate (APP) and DOPO), silica aerogel, aluminum hydroxide, carbon black, and surface-treated coffee grounds in specific proportions, and by processing the composition under a high-shear mixing process and a nitrogen atmosphere. 10 to 20 parts by weight of a phosphor-based flame retardant, 1 to 5 parts by weight of silica aerogel, 1 to 15 parts by weight of aluminum hydroxide, 0.2 to 2 parts by weight of carbon black, and 0.1 to 2 parts by weight of surface-treated coffee grounds are added and dispersed to 100 parts by weight of polyol, and the isocyanate is reacted under conditions of an NCO / OH molar ratio of 1.05 to 1.15. Silica aerogel blocks heat transfer due to its ultra-insulating properties, APP and DOPO systems form a phosphate-based carbon layer upon combustion, aluminum hydroxide reduces flame temperature through endothermic reactions and water vapor release during thermal decomposition, and carbon black maximizes the oxygen blocking effect by reinforcing the high-density carbon layer. The mixing and reaction processes are performed in a nitrogen atmosphere to suppress air ingress and ensure dispersion stability, and foaming is cured at 40 to 70°C for 10 to 60 minutes to ensure the mechanical stability of the product. When 0.1 to 2 parts by weight of surface-treated coffee grounds are added, it provides micropore control, improved dispersibility, and a natural carbon-based reinforcement effect, thereby simultaneously enhancing the structural stability and flame retardancy of the foam. It also improves the quality and functionality of the foam, such as mechanical reinforcement and eco-friendliness, and functions to enhance overall flame retardancy by ensuring dispersibility and acting complementarily with phospho-based flame retardants, silica aerogel, and aluminum hydroxide. Effects of the invention
[0012] The flame-retardant rigid urethane foam according to the present invention secures an Oxygen Index (LOI) of 28 or higher and achieves Class A flame-retardant performance by satisfying a Flame Spread Index (FSI) of 25 or lower and a Smoke Developed Index (SDI) of 450 or lower in the ASTM E84 test. In addition, the internal structure is protected from damage during combustion due to the reinforcement effect of silica aerogel and the carbon layer, and the addition of surface-treated coffee grounds forms an expansive carbon layer during foaming compared to conventional flame-retardant urethane, resulting in a significantly lower generation of smoke and toxic gases. Furthermore, ammonium polyphosphate (APP), 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), aluminum hydroxide [Al(OH)₃], carbon black, and The synergistic effect of surface-treated coffee grounds forms a high-strength carbonized protective film, significantly enhancing structural stability while maintaining or improving thermal insulation performance. This combined effect offers excellent technical applicability in fields requiring high flame retardancy and high performance, such as building insulation, flame-retardant interior materials, and industrial protective panels. Brief explanation of the drawing
[0013] Figure 1 is a manufacturing process diagram of a flame-retardant rigid urethane foam according to the present invention. Specific details for implementing the invention
[0014] The present invention relates to a technology for manufacturing a flame-retardant rigid urethane foam by mixing a polyol composition with a phosphor-based flame retardant (a mixture of APP and DOPO), silica aerogel, aluminum hydroxide, carbon black, and surface-treated coffee grounds in specific proportions, and then adding an isocyanate (NCO / OH molar ratio 1.05~1.15) to foam and cure. The manufacturing process of the present invention includes a polyol mixing step, an air ingress inhibition step, an isocyanate addition step, a foaming and curing step, and a post-treatment step, and these steps are performed sequentially.
[0015] In the polyol mixing step, with respect to 100 parts by weight of polyol, 1 to 5 parts by weight of silica aerogel, 1 to 15 parts by weight of aluminum hydroxide, 10 to 20 parts by weight of phospho-based flame retardant, 0.2 to 2 parts by weight of carbon black, and After adding 0.1 to 2 parts by weight of surface-treated coffee grounds, the mixture is mixed under high-shear conditions for 2 to 5 minutes to ensure that each component is uniformly dispersed without aggregation. Since silica aerogel has super-insulating properties, it inhibits heat transfer within the internal cell structure of the foam, and sufficient shear force must be applied during mixing to ensure it is uniformly distributed within the cell structure. Aluminum hydroxide undergoes endothermic decomposition at 200 to 300°C to generate water vapor, thereby lowering the flame temperature and reducing the combustion rate.
[0016] Coffee grounds contain a number of hydroxyl groups (-OH) on the surface of cellulose and lignin polymers, which allows for bonding with polyurethane; however, due to their moisture-absorbing properties, foaming defects or non-uniformity of bubbles may occur, which raises concerns about a decrease in the mechanical strength of the final product and thus limits their practical application.
[0017] However, in the present invention, it was confirmed that removing moisture through a pretreatment process for coffee grounds and subsequently performing a surface treatment using silane, phosphate, or carboxyl group enhances the chemical bonding strength and dispersibility with polyol, thereby improving the physical properties of the composite material.
[0018] The above pretreatment process consists of three main stages, and
[0019] (1) After drying the coffee grounds in an oven at 100℃ to remove moisture,
[0020] (2) Grind to a size of 50~200 mesh, and
[0021] (3) Surface treatment using silane, etc. is performed. The reaction occurs between the hydroxyl group (Cell-OH) on the surface of the coffee grounds and the alkoxy group (-OR) of the silane as follows.
[0022] Reaction formula: Cell-OH + R-Si(OR)₃ → Cell-O-Si-R + 3ROH
[0023] As described above, the fine particles of the surface-treated coffee grounds influence bubble formation during the foaming process, thereby reducing the pore size of the bubbles or improving the uniformity of the bubbles, and form an expansive carbon layer during foaming to reduce smoke generation, and provide antibacterial, deodorizing, and hygroscopic functions, while the phospho-based flame retardant containing APP and DOPO generates a phosphate intermediate by heat to promote the formation of the carbon layer, and the carbon black enhances the oxygen blocking effect by increasing the density and mechanical strength of the carbon layer.
[0024] In the air inflow suppression step, the mixing process is performed under a nitrogen atmosphere to prevent oxygen from the outside air from entering the reaction system. This is intended to maintain the dispersion stability of the flame retardant and fine powder, and to minimize viscosity fluctuations during the foaming reaction. Maintaining a nitrogen atmosphere inhibits the oxidation reaction of the reaction mixture and preserves the thermal stability of the flame retardant, allowing the components to function as intended after foaming.
[0025] In the isocyanate addition step, isocyanate is added to the polyol mixture in such a way that the NCO / OH molar ratio is 1.05 to 1.15, and then uniform reactivity is ensured through rapid stirring. Since the hardness, mechanical strength, and cell structure uniformity of the foam may decrease if the molar ratio deviates excessively from the range, it is important to maintain the above range.
[0026] In the foaming and curing step, the mixed reaction solution is injected into a mold or panel board to foam it, and then cured at a temperature of 40 to 70°C for 10 to 60 minutes to form the final structure. The curing time is adjusted according to the thickness and shape of the product; at excessively low temperatures, foaming becomes incomplete, and at excessively high temperatures, cell collapse and a decrease in strength may occur.
[0027] In the post-processing stage, the cured foam is cut, processed, or surface-treated according to the purpose to produce the final product form. Durability or surface flame-retardant performance may also be enhanced by applying an additional surface coating layer.
[0028] The feasibility of performing a specific manufacturing process is described below through an example according to the present invention.
[0029] <Example 1> Preparation of foam based on standard composition
[0030] 100 parts by weight of polyol were mixed with 3 parts by weight of silica aerogel, 10 parts by weight of aluminum hydroxide, 15 parts by weight of APP / DOPO mixed flame retardant, 1 part by weight of carbon black, and 1 part by weight of surface-treated coffee grounds in a high-shear mixer for 3 minutes. Subsequently, isocyanate was added under a nitrogen atmosphere to achieve an NCO / OH molar ratio of 1.10, and the reaction was carried out rapidly. Foaming was performed at 50°C for 30 minutes. The manufactured foam met Class A standards, exhibiting an LOI of 29, an ASTM E84 Flame Spread Index of 20, and a Smoke Developed Index of 430. In the combustion test, a uniform surface carbonization layer was formed, and internal cell protection was confirmed without structural collapse.
[0031] <Example 2> Preparation of a composition with enhanced thermal insulation properties
[0032] The silica aerogel content was increased to 5 parts by weight for 100 parts by weight of polyol, and the APP / DOPO mixture was set to 12 parts by weight. As a result of performing the process under the same conditions, the thermal conductivity of the foam was reduced by approximately 8% compared to the conventional urethane foam, and the flame retardant performance showed an LOI of 28 and an FSI of 23. The effect of improved thermal insulation due to the increase in aerogel was confirmed, and the formation of the carbonized layer was similar to that of Example 1.
[0033] <Example 3> Preparation of a composition for enhancing the formation of a high carbonization layer
[0034] As a result of manufacturing a foam under the same conditions as Example 1 by increasing the carbon black to 2 parts by weight, the density and compressive strength of the surface carbonized layer increased during combustion, and the combustion rate was significantly reduced. The amount of smoke generated was also reduced, with FSI at 18 and SDI at 410. This was analyzed as a result of the synergistic effect between the carbon black and the APP / DOPO system.
[0035] <Comparative Example 1> No phosphoric flame retardant added
[0036] When manufactured with the same composition excluding APP / DOPO, the LOI decreased to 22, and a stable carbide layer was not formed due to surface collapse during combustion. As a result, the FSI increased to 45.
[0037] <Comparative Example 2> Silica aerogel not added
[0038] The foam manufactured without aerogel exhibited increased thermal conductivity, and the internal cell structure was rapidly exposed to heat and damaged during combustion. The LOI was reduced to 24 and failed to meet the ASTM E84 Class A standard.
[0039] The above examples are intended to illustrate the technical concept of the present invention, and the composition ratio, curing conditions, type of flame retardant, etc., can be applied with various modifications as long as they do not deviate from the scope of the invention.
Claims
Claim 1 Based on 100 parts by weight of polyol, 10 to 20 parts by weight of phospho-based flame retardants including ammonium polyphosphate (APP) and 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), 1 to 5 parts by weight of silica aerogel, 1 to 15 parts by weight of aluminum hydroxide, and 0.2 to 2 parts by weight of carbon black. A flame-retardant rigid urethane foam characterized by being composed of 0.1 to 2 parts by weight of surface-treated coffee grounds and forming a closed-cell structure through a foaming reaction. Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 The flame-retardant rigid urethane foam according to claim 1, characterized in that the surface-treated coffee grounds are dried in an oven at 100°C to remove moisture, then ground to a size of 50 to 200 mesh, and surface-treated using silane. Claim 6 delete Claim 7 delete Claim 8 A polyol mixing step comprising adding 1 to 5 parts by weight of silica aerogel, 1 to 15 parts by weight of aluminum hydroxide, 10 to 20 parts by weight of phospho-based flame retardants (ammonium polyphosphate (APP) and 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO)), 0.2 to 2 parts by weight of carbon black, and 0.1 to 2 parts by weight of surface-treated coffee grounds to 100 parts by weight of polyol, and mixing in a high-shear mixer for 2 to 5 minutes to form a polyol mixture in which each component is uniformly dispersed without aggregation; an oxygen inflow blocking step comprising performing the polyol mixing step under a nitrogen atmosphere to prevent the inflow of oxygen from external air; an isocyanate addition step comprising adding isocyanate to the polyol mixture such that the NCO / OH molar ratio is 1.05 to 1.15; injecting the polyol mixture with added isocyanate into a mold or panel board to foam, and 40 to A method for manufacturing a flame-retardant rigid urethane foam, characterized by comprising: a foaming and curing step of curing at 70°C for 10 to 60 minutes; and a post-treatment step of cutting, processing, or surface treating the cured foam. Claim 9 A method for manufacturing a flame-retardant rigid urethane foam according to claim 8, characterized in that the APP / DOPO mixture flame retardant is pre-dispersed in a high-speed shear mixer under conditions of 800 to 1500 rpm for 3 to 10 minutes and then added to a polyol.
Citation Information
Patent Citations
Environment-friendly degradable polymer foam material and preparation method thereof
CN116462824A
Manufacture of rigid polyurethane
JP1990138328A
Flame retardant hard polyurethane foam
KR1020180063111A
How to make shoes member that are environmentally friendly and upcyclable, members for shoes manufactured therefrom
KR102279221B1
